Degradable foam box for cold chain and preparation method thereof
The degradable cold chain foam box prepared by composite materials and supercritical CO2 foaming technology solves the problems of difficulty in degradation, low compressive strength and poor insulation performance of traditional foam boxes, and achieves efficient degradation and excellent physical properties. It is suitable for fresh food distribution and cold chain packaging.
Patent Information
- Application Number
- CN202511065325.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-08-29
- Estimated Expiration
- 2045-07-31
AI Technical Summary
The existing foam box materials for cold chains have problems such as difficulty in degradation, low compressive strength and poor thermal insulation performance, and it is difficult to meet the requirements of green and environmental protection.
A composite material of thermoplastic starch particles, modified polylactic acid particles, modified bamboo fibers, maleic anhydride polyester elastomers, plasticizers and plastic degradation toughening agents is prepared by supercritical CO2 foaming technology. The modified bamboo fibers are modified by nano-calcium carbonate and cellulose nanocrystal particles to enhance the interface binding force.
The prepared foam box disintegrated significantly in natural soil within 90 days. The degradation rate in 60 days exceeds 80% in compost environment, the compression strength is ≥120KPa, the water absorption rate is ≤1.5% in 24 hours, the thermal conductivity is ≤0.021W/(m·K), the insulation time is as high as 1400min, and it has excellent compressive strength and insulation properties.
Smart Images

Figure CN120554716A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of foam box materials, and in particular relates to a degradable foam box for cold chain and a preparation method thereof. Background Art
[0002] In recent years, due to the rapid development of e-commerce, the demand for cold chain logistics has continued to increase. Cold chain logistics refers to a supply chain system in which perishable and perishable products such as food and medicine are always kept in a specified low-temperature environment throughout the production, storage, transportation, sales and consumption to ensure product quality, reduce losses and prevent pollution.
[0003] In order to extend the insulation time, foam boxes with good thermal insulation are one of the packaging materials for cold chain logistics. The material of traditional foam boxes is mainly polystyrene foam. Although it is light in weight and high in strength, it is difficult to degrade and does not meet the requirements of green environmental protection. Therefore, it is of great significance to use new degradable materials to replace polystyrene foam.
[0004] A prior art Chinese patent, authorized with publication number CN116102766B, discloses an ultra-light, highly flame-retardant biodegradable PLA foam and its preparation process. The preparation process includes the following steps: Step S1: Compounding RDP, lignin, APP, and silica aerogel to produce a flame-retardant system; Step S2: Mixing PLA, PBAT, the flame-retardant system, and an epoxy chain extender to produce a mixed sample after the reaction; Step S3: Placing the mixed sample in a molding apparatus to form a molded sample; Step S4: Supercritical foaming the molded sample under a carbon dioxide atmosphere to produce a foamed sample; Step S5: Cooling the foamed sample to form the ultra-light, highly flame-retardant biodegradable PLA foam. The PLA foam produced by this invention has low density, low thermal conductivity, excellent flame retardancy, and is fully biodegradable. It is widely applicable to packaging, insulation, and shock absorption applications such as express packaging, cold chain packaging, vaccine packaging, exterior wall insulation, and interior decoration. However, this technical solution does not address compressive strength.
[0005] In the master's thesis (Zhang Yu. Preparation and performance research of gelatin-based degradable foam for cold chain transport packaging [D] Xi'an University of Technology, 2020.), gelatin and starch were used as raw materials for buffering and thermal insulation foam materials, and a process route for degradable gelatin-based degradable foam materials was established. The influence and influencing mechanism of the preparation process on the structure, mechanical properties and thermal properties of gelatin-based foam were systematically analyzed, and the feasibility of the application of gelatin-based foam in cold chain transport packaging was explored. However, the compressive strength of this technical solution is low and the thermal insulation performance is poor. Summary of the Invention
[0006] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art and at least provide a beneficial alternative. Specifically, the present invention provides a degradable cold chain foam box and a preparation method thereof. The degradable cold chain foam box meets the basic performance requirements of degradable materials and has good composting ability, making it suitable for use in scenarios such as fresh food delivery and cold chain packaging.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] In the first aspect, the present invention provides a degradable foam box for cold chain, which comprises, by mass, 70-90 parts of thermoplastic starch particles, 10-30 parts of modified polylactic acid particles, 10-20 parts of modified bamboo fiber, 2-5 parts of maleic anhydride polyester elastomer, 1-3 parts of plasticizer, 1-3 parts of plastic degradation toughening agent, and 0.5-1 part of nucleating agent; the modified bamboo fiber is bamboo fiber modified with nano-calcium carbonate and cellulose nanocrystal particles.
[0009] The thermoplastic starch granules described in the present invention are also called "unstructured starch". They are made by disordering the starch structure through a certain method to make it thermoplastic. They are commercially available products and can be sourced from Suzhou Corning Polyol Co., Ltd. or Suzhou Minghua Sugar Alcohol Co., Ltd.
[0010] Optionally, the mass fraction of the thermoplastic starch particles can be any value among 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, or a range value consisting of any two values.
[0011] Preferably, the modified polylactic acid particles are Bio-plus 301p produced by Guangzhou Bijia Material Technology Co., Ltd.
[0012] Optionally, the mass fraction of the modified polylactic acid particles can be any value among 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, or a range value consisting of any two values.
[0013] Preferably, the preparation method of the modified bamboo fiber comprises the following steps: alkali-treating the bamboo fiber to obtain pretreated bamboo fiber; dispersing nano-calcium carbonate and cellulose nanocrystal particles in an ethanol aqueous solution, adding a silane coupling agent to obtain a suspension; adding the pretreated bamboo fiber to the suspension for immersion, and drying to obtain the modified bamboo fiber.
[0014] Preferably, the mesh size of the bamboo fiber is 100-150 meshes.
[0015] Optionally, the mesh number of the bamboo fiber can be any value among 100 mesh, 120 mesh, 140 mesh, 150 mesh, or a range value consisting of any two values.
[0016] Preferably, the alkali treatment method is: soaking the bamboo fiber in a sodium hydroxide solution with a concentration of 5-10wt% for 30-60min, washing with water until neutral, and drying the pretreated bamboo fiber.
[0017] Preferably, the mass ratio of the nano-calcium carbonate, the cellulose nanocrystal particles, the silane coupling agent and the ethanol aqueous solution is 3-6:2-4:1.5-2.5:25-35.
[0018] Preferably, the mass ratio of the nano-calcium carbonate, the cellulose nanocrystal particles, the silane coupling agent and the ethanol aqueous solution is 5:3:2:30.
[0019] Preferably, the ethanol aqueous solution is a mixture of ethanol and water in a mass ratio of 60-80:20-40.
[0020] Preferably, the silane coupling agent is KH550.
[0021] Preferably, the mass volume ratio of the pretreated bamboo fiber to the suspension is 1-2 g: 200-300 mL.
[0022] Preferably, the nano-calcium carbonate is cubic nano-calcium carbonate with a particle size of 100-500 nm.
[0023] Optionally, the particle size of the nano-calcium carbonate can be any point value among 100nm, 200nm, 300nm, 400nm, 500nm, or a range value consisting of any two point values.
[0024] Preferably, the particle size of the cellulose nanocrystal particles is 50-100 nm.
[0025] Optionally, the particle size of the cellulose nanocrystal particles can be any point value among 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or a range value consisting of any two point values.
[0026] Optionally, the mass percentage of the modified bamboo fiber can be any value among 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, or a range value consisting of any two values.
[0027] Optionally, the weight percentage of the maleated polyester elastomer can be any value among 2 parts, 3 parts, 4 parts, 5 parts, or a range consisting of any two values.
[0028] Preferably, the plasticizer is selected from at least one of glycerol, ethylene glycol, sorbitol and xylitol.
[0029] Optionally, the mass fraction of the plasticizer may be any value among 1 part, 2 parts, 3 parts, or a range value consisting of any two values.
[0030] Preferably, the plastic degradation toughening agent is HB820 and / or HB320 produced by Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.
[0031] Optionally, the mass fraction of the plastic degradation toughening agent can be any value among 1 part, 2 parts, 3 parts, or a range value consisting of any two values.
[0032] Preferably, the nucleating agent is a degradable nucleating agent.
[0033] Preferably, the degradable nucleating agent is RQT-CH-6 or RQT-CH-8 produced by Henan Ruiqi Chemical Co., Ltd.
[0034] Optionally, the mass fraction of the nucleating agent can be any value among 0.5 part, 0.7 part, 0.9 part, 1 part, or a range value consisting of any two values.
[0035] In a second aspect, the present invention provides a method for preparing the above-mentioned degradable cold chain foam box, comprising the following steps:
[0036] S1, mixing thermoplastic starch particles, modified polylactic acid particles, modified bamboo fiber, maleic anhydride polyester elastomer, plasticizer, plastic degradation toughening agent, and nucleating agent, extruding, and pelletizing to obtain foaming masterbatch;
[0037] S2. Place the foaming masterbatch in a foaming mold, place the mold in a high-pressure foaming reactor for supercritical CO2 foaming, and release the pressure and cool to obtain the product.
[0038] Preferably, the supercritical CO2 foaming conditions are: temperature of 120-150° C., pressure of 15-25 MPa, and time of 2-4 h.
[0039] Optionally, the foaming conditions of the supercritical CO2 foaming are: the temperature can be any point value among 120℃, 130℃, 140℃, 150℃ or a range value consisting of any two point values; the pressure can be any point value among 15MPa, 18MPa, 20MPa, 22MPa, 25MPa or a range value consisting of any two point values; the time can be any point value among 2h, 3h, 4h or a range value consisting of any two point values.
[0040] Preferably, the pressure relief rate is 10-30 MPa / s.
[0041] Optionally, the pressure relief rate may be any value among 10 MPa / s, 20 MPa / s, 30 MPa / s, or a range value consisting of any two values.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) The present invention uses biodegradable thermoplastic starch particles and modified polylactic acid particles as the main foaming components to provide a degradable cold chain foam box. After degradation test, it was found that the box disintegrated significantly in natural soil within 90 days, the degradation rate was greater than 80% in a composting environment within 60 days, and the box completely disintegrated after being immersed in seawater for 120 days.
[0044] (2) The present invention proposes that the compressive strength of the degradable cold chain foam box obtained by compounding modified bamboo fiber, maleic anhydride polyester elastomer and plastic degradation toughening agent is ≥120KPa, the 24h water absorption rate is ≤1.5%, the thermal conductivity is ≤0.021W / (m·K), and the heat preservation time can be as high as 1400min; wherein the modified bamboo fiber is modified by cubic nano-calcium carbonate and cellulose nanocrystal particles, which are loaded on the surface of the bamboo fiber, the cubic nano-calcium carbonate provides rigidity, and the cellulose nano-crystal particles provide the rigidity. The hydrogen bonding effect of the crystal particles enables the bamboo fiber to form a hydrogen bonding network with the thermoplastic starch particles and modified polylactic acid particles, thereby enhancing the interfacial bonding force; under the action of the maleic anhydride polyester elastomer, the thermoplastic starch particles, modified polylactic acid particles and modified bamboo fiber can achieve optimal compatibility, avoiding the agglomeration of the modified bamboo fiber. At the same time, by adding a specific plastic degradation toughening agent, after supercritical CO2 foaming, a uniform and dense closed-cell structure can be formed, which enables the foam box to withstand greater external forces without being easily destroyed and has excellent thermal insulation properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a physical picture of the degradable cold chain foam box prepared in Example 1;
[0046] Figure 2 is the SEM image of bamboo fiber before modification;
[0047] Figure 3 This is the SEM image of the modified bamboo fiber prepared in Preparation Example 1;
[0048] Figure 4 This is the SEM image of the modified bamboo fiber prepared in Preparation Example 2;
[0049] Figure 5 This is the SEM image of the modified bamboo fiber prepared in Preparation Example 3;
[0050] Figure 6 and Figure 7 This is a graph showing the thermal insulation performance test results of the degradable cold chain foam box prepared in Example 2. DETAILED DESCRIPTION
[0051] The present invention is described in detail below with reference to specific embodiments. The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the inventive concept. These all fall within the scope of protection of the present invention. Unless otherwise specified, the raw materials, reagents, or devices used in the Examples of the present invention and the Comparative Examples can be obtained from conventional commercial sources or can be obtained by existing known methods.
[0052] Preparation Example 1 Preparation of modified bamboo fiber 1:
[0053] The preparation method of modified bamboo fiber 1 is as follows: bamboo fiber is soaked in a sodium hydroxide solution with a concentration of 6wt% for 50 minutes, washed with water until neutral, and dried to pretreat the bamboo fiber; nano-calcium carbonate and cellulose nanocrystal particles are dispersed in an ethanol aqueous solution (a mixture of ethanol and water with a mass ratio of 70:30), and a silane coupling agent KH550 is added to obtain a suspension; pretreated bamboo fiber is added to the suspension and immersed, and the modified bamboo fiber is obtained after drying.
[0054] The mesh number of the bamboo fiber is 120 mesh, and it comes from Guangdong Limei New Material Technology Co., Ltd., model: BF-2120.
[0055] The nano calcium carbonate is cubic nano calcium carbonate with a particle size of 200-300 nm, which is sourced from Nanjing Hongde Nanomaterials Co., Ltd., model: HDYZ22.
[0056] The particle size of cellulose nanocrystal particles is 77 nm, and they are from Shenzhen Jieling New Materials Co., Ltd., model: NCC100.
[0057] The mass ratio of the nano-calcium carbonate, the cellulose nano-crystal particles, the silane coupling agent and the ethanol aqueous solution is 5:3:2:30.
[0058] The mass volume ratio of the pretreated bamboo fiber and the suspension is 1 g:250 mL.
[0059] The SEM image of bamboo fiber before modification is as follows Figure 2 As shown; the SEM image of modified bamboo fiber 1 is as shown Figure 3 shown.
[0060] Preparation Example 2 Preparation of modified bamboo fiber 2:
[0061] The preparation method of modified bamboo fiber 2 is as follows: the bamboo fiber is soaked in a sodium hydroxide solution with a concentration of 6wt% for 50 minutes, washed with water until neutral, and dried to pretreat the bamboo fiber; cellulose nanocrystal particles are dispersed in an ethanol aqueous solution (a mixture of ethanol and water with a mass ratio of 70:30), and a silane coupling agent KH550 is added to obtain a suspension; the pretreated bamboo fiber is added to the suspension and immersed, and then dried to obtain the modified bamboo fiber.
[0062] The mesh number of the bamboo fiber is 120 mesh, and it comes from Guangdong Limei New Material Technology Co., Ltd., model: BF-2120.
[0063] The particle size of cellulose nanocrystal particles is 77 nm, and they are from Shenzhen Jieling New Materials Co., Ltd., model: NCC100.
[0064] The mass ratio of the cellulose nanocrystal particles, the silane coupling agent and the ethanol aqueous solution is 8:2:30.
[0065] The mass volume ratio of the pretreated bamboo fiber and the suspension is 1 g:250 mL.
[0066] The SEM image of modified bamboo fiber 2 is shown in Figure 2. Figure 4 shown.
[0067] Preparation Example 3 Preparation of modified bamboo fiber 3
[0068] The preparation method of modified bamboo fiber 3 is as follows: the bamboo fiber is soaked in a sodium hydroxide solution with a concentration of 6wt% for 50 minutes, washed with water until neutral, and dried to pretreat the bamboo fiber; nano-calcium carbonate is dispersed in an ethanol aqueous solution (a mixture of ethanol and water with a mass ratio of 70:30), and a silane coupling agent KH550 is added to obtain a suspension; the pretreated bamboo fiber is added to the suspension and immersed, and then dried to obtain the modified bamboo fiber.
[0069] The mesh number of the bamboo fiber is 120 mesh, and it comes from Guangdong Limei New Material Technology Co., Ltd., model: BF-2120.
[0070] The nano calcium carbonate is cubic nano calcium carbonate with a particle size of 200-300 nm, which is sourced from Nanjing Hongde Nanomaterials Co., Ltd., model: HDYZ22.
[0071] The mass ratio of the nano-calcium carbonate silane coupling agent to the ethanol aqueous solution is 8:2:30.
[0072] The mass volume ratio of the pretreated bamboo fiber and the suspension is 1 g:250 mL.
[0073] The SEM image of modified bamboo fiber 3 is shown in Figure 2. Figure 5 shown.
[0074] The raw materials used in the following examples and comparative examples are all commercially available, but are not limited to these materials:
[0075] Thermoplastic starch granules: from Suzhou Corning Polyol Co., Ltd.
[0076] Modified polylactic acid particles: Bio-plus 301p from Guangzhou Bijia Material Technology Co., Ltd.
[0077] Maleic anhydride polyester elastomer: from Coase Chemical Co., Ltd., model: BP-1;
[0078] Maleic anhydride grafted polyolefin elastomer: Fusabond N495 from DuPont;
[0079] Plastic degradation toughening agent: HB820 from Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.
[0080] Degradable nucleating agent: RQT-CH-6 from Henan Ruiqi Chemical Co., Ltd.
[0081] Degradable foam boxes for cold chain use were prepared in Example 1-Example 3 and Comparative Example 1-Comparative Example 5. The compositions, in parts by mass, are shown in Table 1 below.
[0082] Table 1
[0083]
[0084] The preparation method comprises the following steps: according to Table 1, S1, mixing thermoplastic starch particles, modified polylactic acid particles, modified bamboo fiber, maleic anhydride polyester elastomer or maleic anhydride grafted polyolefin elastomer, plasticizer, plastic degradation toughening agent, and degradable nucleating agent, extruding, and pelletizing to obtain foaming masterbatch;
[0085] S2. Place the foaming masterbatch in a foaming mold, place the mold in a high-pressure foaming reactor for supercritical CO2 foaming (foaming conditions: temperature 130°C, pressure 20 MPa, time 3 h), and release the pressure and cool at a rate of 25 MPa / s.
[0086] Test Example 1:
[0087] The following performance tests were performed on the degradable cold chain foam boxes prepared in Examples 1 to 3 and Comparative Examples 1 to 5:
[0088] 1. Compression strength (10%): tested according to GB / T 8813-2020;
[0089] 2. Water absorption: tested according to GB / T 8810-2005;
[0090] 3. Thermal conductivity: Tested according to GB / T 10297-2015, with the inside temperature at 12°C and the outside temperature at 50°C. The results are shown in Table 2.
[0091] Table 2
[0092]
[0093] As can be seen from Table 2, the foam boxes prepared in Examples 1-3 have excellent physical properties, with compression strength ≥120 KPa, 24h water absorption ≤1.5%, and thermal conductivity ≤0.021 W / (m·K);
[0094] Comparative Example 1 has no nano-calcium carbonate in the modified bamboo fiber 2, Comparative Example 2 has no cellulose nanocrystal particles in the modified bamboo fiber 3, Comparative Example 3 has no modified bamboo fiber, and Comparative Example 4 has no maleic anhydride polyester elastomer replaced by maleic anhydride grafted polyolefin elastomer.
[0095] In Comparative Example 5, due to the absence of the plastic degradation toughening agent, the compressive strength of the foam box prepared was reduced; the water absorption rate and thermal conductivity were increased, indicating that the physical properties were reduced.
[0096] Test Example 2
[0097] The thermal insulation performance of the degradable cold chain foam box prepared in Example 2 was tested:
[0098] (1) Place the foam box and the foam box with a bag of ice at -25℃, 0℃, 25℃, and 40℃ respectively; the humidity is 50%. Use a temperature recorder to test the temperature changes. The results are as follows Figure 6 As shown;
[0099] (2) Place the foam box and add 1-4 bags of ice at 25℃ and 50% humidity respectively, and use a temperature recorder to test the temperature change. The results are as follows: Figure 7 shown.
[0100] Depend on Figure 6 and Figure 7 It can be seen that the foam box prepared in Example 2 of the present invention has excellent thermal insulation performance at different temperatures, and the thermal insulation time can be as high as 1400 minutes.
[0101] Test Example 3
[0102] The degradation performance and safety and environmental protection tests were performed on the degradable cold chain foam box prepared in Example 2. The degradation performance results are shown in Table 3, and the safety and environmental protection performance are shown in Table 4.
[0103] Table 3
[0104]
[0105] Table 4
[0106]
[0107] It can be seen from Table 3 and Table 4 that the foam box prepared in Example 2 of the present invention has excellent degradation performance and safety performance.
[0108] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A degradable foam box for cold chain, characterized in that: The composition comprises, by weight, 70-90 parts of thermoplastic starch particles, 10-30 parts of modified polylactic acid particles, 10-20 parts of modified bamboo fiber, 2-5 parts of maleic anhydride polyester elastomer, 1-3 parts of plasticizer, 1-3 parts of plastic degradation toughening agent, and 0.5-1 part of nucleating agent. The modified polylactic acid particles are Bio-plus 301p produced by Guangzhou Bijia Material Technology Co., Ltd. The modified bamboo fiber is bamboo fiber modified with nano calcium carbonate and cellulose nano crystal particles.
2. The degradable cold chain foam box according to claim 1, characterized in that: The preparation method of the modified bamboo fiber comprises the following steps: alkali-treating the bamboo fiber to obtain pretreated bamboo fiber; dispersing nano-calcium carbonate and cellulose nano-crystal particles in an ethanol aqueous solution, adding a silane coupling agent to obtain a suspension; adding the pretreated bamboo fiber into the suspension for immersion, and drying to obtain the modified bamboo fiber.
3. The degradable cold chain foam box according to claim 2, characterized in that: The mass ratio of the nano-calcium carbonate, the cellulose nano-crystal particles, the silane coupling agent and the ethanol aqueous solution is 3-6:2-4:1.5-2.5:25-35.
4. The degradable cold chain foam box according to claim 2, characterized in that: The nano calcium carbonate is cubic nano calcium carbonate with a particle size of 100-500nm.
5. The degradable cold chain foam box according to claim 2, characterized in that: The particle size of the cellulose nanocrystal particles is 50-100 nm.
6. The degradable cold chain foam box according to claim 1, characterized in that: The plastic degradation toughening agent is HB820 and / or HB320 produced by Guangzhou Anmi Micro-Nano New Materials Co., Ltd.
7. The degradable cold chain foam box according to claim 1, characterized in that: The nucleating agent is a degradable nucleating agent; the degradable nucleating agent is RQT-CH-6 or RQT-CH-8 produced by Henan Ruiqite Chemical Co., Ltd.
8. The method for preparing the degradable cold chain foam box according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing thermoplastic starch particles, modified polylactic acid particles, modified bamboo fiber, maleic anhydride polyester elastomer, plasticizer, plastic degradation toughening agent, and nucleating agent, extruding, and pelletizing to obtain foaming masterbatch; S2. Place the foaming masterbatch in a foaming mold, place the mold in a high-pressure foaming reactor for supercritical CO2 foaming, and release the pressure and cool to obtain the product.
9. The method for preparing the degradable cold chain foam box according to claim 8, characterized in that: The foaming conditions of the supercritical CO2 foaming are: temperature of 120-150°C, pressure of 15-25 MPa, and time of 2-4 hours.
Citation Information
Patent Citations
Light starch-based high toughness composite foamed material
CN105461967A
High-strength heat-preserving foam box and forming process thereof
CN112722510A
Degradable material and preparation method thereof
CN112724613A
Full-biomass full-degradable material and preparation method and application thereof
CN113683874A
Degradable material and preparation method thereof
CN113754994A